Mechanical milled doped Zn-based semiconductors powders for photovoltaic devices - Laborde, J.I. (2014)
Structural characterization of nanocrystalline Al-doped ZnTe semiconductors, obtained by mechanical milling from ZnTe and Al 2O3 powders, is presented. The samples were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray absorption full spectroscopy (XAFS) and positron annihilation lifetime (PALS) measurements. The results suggested that Al atoms are substitutional incorporated into the ZnTe cubic structure.